2019
DOI: 10.1093/geronb/gbz084
|View full text |Cite
|
Sign up to set email alerts
|

Retracted and replaced: The Impact of Learning Multiple Real-World Skills on Cognitive Abilities and Functional Independence in Healthy Older Adults

Abstract: Objective The natural learning experience from infancy to emerging adulthood, when considerable cognitive and functional growth is observed, mandates learning multiple real-world skills simultaneously. The present studies investigated whether learning multiple real-world skills simultaneously is possible in older adults and also whether it improves both their cognitive abilities (working memory, episodic memory, and cognitive control) and functional independence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
2
24
1
Order By: Relevance
“…We argue that the novelty and challenge of the specific leisure activities critically moderates the potential Human Development 2021;65:51-64 DOI: 10.1159/000514554 cognitive benefits (e.g., Leanos et al, 2020;Park et al, 2014;Stine-Morrow, 2007), and variety is likely important as well (e.g., Carlson et al, 2012). For example, some older adults may engage in new learning in their leisure pursuits (e.g., Marzorati, 2016).…”
Section: The Impact Of Learning and Motivation After Retirementmentioning
confidence: 99%
See 3 more Smart Citations
“…We argue that the novelty and challenge of the specific leisure activities critically moderates the potential Human Development 2021;65:51-64 DOI: 10.1159/000514554 cognitive benefits (e.g., Leanos et al, 2020;Park et al, 2014;Stine-Morrow, 2007), and variety is likely important as well (e.g., Carlson et al, 2012). For example, some older adults may engage in new learning in their leisure pursuits (e.g., Marzorati, 2016).…”
Section: The Impact Of Learning and Motivation After Retirementmentioning
confidence: 99%
“…Therefore, low expectations could lead older adults to be on trajectories where they underperform over time because of setting the bar too low. Some interventions have been developed with older adults to mitigate the impact of low expectations (e.g., Leanos et al, 2020;West et al, 2008), although more research is needed to better understand the needs and barriers of older adults in circumstances that yield low expectations, especially with regard to learning new skills and content.…”
Section: The Impact Of Low Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Park et al (2014) found that older adults who learned new skills such as quilting or photography also demonstrated increased episodic memory abilities. Leanos et al (2020) found that simultaneously learning multiple novel skills was feasible for older adults and also resulted in improvements in cognitive abilities. Evidence also suggests that engagement in cognitive activities may protect against cognitive decline ( Edwards et al, 2017 ; Fratiglioni et al, 2004 ) and may lead to increases in learning self-efficacy and instill confidence in older adults that they can take on new learning challenges ( Nguyen et al, 2020 ).…”
mentioning
confidence: 99%